Pituitary Dysfunction after Brain Injury: https://doi.org/10.59156/revista.v37i02.507 - Mariela, Luna; Nicole, Lemaitre; Liz, Ruiz; Ulloque Caamaño, Liezel; Cano Rocío, Reyes; Funes, Tomas; Campero, Álvaro (Revista Argentina de Neurocirugía, 2023)
Background. Hypopituitarism is an event that must be detected early in patients with head injuries, due to the high associated morbidity and mortality. Objectives. To analyze the pituitary dysfunction after a head injury and the correlation between the severity and the hormonal alterations found. Methods. Observational and prospective study. 101 patients hospitalized in the Neurosurgery and Intensive Care Unit of "Ángel C. Padilla" Hospital in San Miguel de Tucumán, Argentina, between May 1 and June 30, 2021. Demographic data, score of Glasgow coma, associated injuries, hypothalamic-pituitary hormone determination and blood sodium levels were recorded in the first 7 days after brain injury. Results. A total of 83 men and 18 women were affected with predominant involvement between 20-29 years (36.6%). Mild head trauma affected 7.9%, moderate 59.4%, and severe 32.7%. The most frequently described structural lesion was contusion (43.6%). 83.2% of all patients had a normal dose of corticotropin, while in 11.9% it was low; High cortisol was recorded in 43.5% of the patients and low in 10% of the cases. Testosterone was reduced by 42.6% and the rest of the pituitary hormones had no significant changes. ACTH was low in 11.9% of severe trauma with hypernatremia in 22%. Conclusion. There is a relationship between the severity of traumatic brain injury and pituitary dysfunction, with major severity of trauma associated to corticotropin deficiency and hypernatremia. Keywords. Glasgow coma score; hypopituitarism; pituitary dysfunction; traumatic brain injury.
Keywords: Glasgow coma score; hypopituitarism; pituitary dysfunction; traumatic brain injury